Oculomotor dynamics in skilled soccer players: The effects of sport expertise and strenuous physical effort - Zwierko, T.; Jedziniak, W.; Florkiewicz, B.; Stepinski, M.; Buryta, R.; Kostrzewa-Nowak, D.; Nowak, R.; Popowczak, M.; Wozniak, J. (European Journal of Sport Science, 2019)
The ability to quickly locate objects within the visual field has a significant influence on athletic performance. Saccades are conjugate eye movements responsible for the rapid shift that brings a new part of the visual field into foveal vision. The aim of this study was to investigate the effects of sport expertise and intense physical effort on saccade dynamics during a free-viewing visual search task in skilled soccer players. Two groups of male subjects participated in this study: 18 soccer players and 18 non-athletes as the control group. Two sessions of visual search tasks without a sport-specific design were employed. Eye movements during the visual search tasks were recorded binocularly. Between pre- and post-test sessions, athletes performed a maximal incremental treadmill test. Cardiorespiratory parameters were measured continuously. Capillary lactate samples were collected. Pre-test findings indicated that athletes, in comparison to non-athletes, achieve higher values of the following characteristics of saccades (1) average acceleration, (2) acceleration peak, (3) deceleration peak, and (4) average velocity. An increase in post-test saccade duration and a decrease in post-test saccade velocity was observed in athletes due to the strenuous physical effort in relation to the pre-test state. Athletes may transfer high saccadic function efficiency to non-specific visual stimuli. The findings partially confirm that physical exertion can reduce oculomotor efficiency in athletes.